Bacteriological profile and antibiotic sensitivity pattern in sputum culture of chronic obstructive pulmonary disease patients - B. L., Shashibhushan; C., Nagaraja; B. J., Arun; Nagaraj, Niranjan (International Journal of Advances in Medicine, 2016)
Background: Chronic obstructive pulmonary disease (COPD) is a common disease characterized by persistent airflow obstruction with an enhanced chronic inflammatory response in the airways and the lung to noxious particles or gases. The aim of the present study was to obtain comprehensive insight into the bacteriological profile and antibiotic sensitivity pattern in sputum culture of COPD patients. Methods: A retrospective observational study was carried out at Bangalore medical college, Bangalore which comprised of 100 patients diagnosed with chronic obstructive pulmonary disease from June 2015 to July 2015. Sputum culture and sensitivity reports were retrospectively analysed for the bacteriological profile and their antimicrobial sensitivity pattern. Results: Hundred patients diagnosed with COPD included with the age group comprising from 40 to >80 years of age, most common pathogenic bacteria isolated was Streptococcus pneumonia (42%), followed by Pseudomonas aerogionsa (23%), Klebsiella (15%), E coli (12%), GNNF (7%) and citorbacter (1%). Ceftriaxone was the most effective antibiotic against Streptococcus pneumonia. Conclusions: Streptococcus pneumoniae was the most common pathogen in COPD patients, and ceftriaxone was most effective antibiotic against the most of the organism. Ceftriaxone should be the first line empirical antibiotic.